Assessment of the immunogenicity and protection of a Nipah virus soluble G vaccine candidate in mice and pigs - Gao, Zihan; Li, Tao; Han, Jicheng; Feng, Sheng; Li, Letian; Jiang, Yuhang; Xu, Zhiqiang; Hao, Pengfei; Chen, Jing; Hao, Jiayi; Xu, Peng; Tian, Mingyao; et al. (Frontiers in Microbiology, 2022)
Nipah virus (NiV) is a newly emerged extremely dangerous zoonotic pathogen highly fatal to humans. Currently, no approved vaccine is available against NiV. This study employed a mammalian eukaryotic system to express NiV soluble G glycoprotein (NiV-sG), using CpG oligodeoxynucleotides (CpG)/Aluminum salt (Alum) as adjuvants to obtain a recombinant subunit vaccine candidate. We also evaluated the immunogenicity and efficacy of the protein in mice and pigs. A neoadjuvant (HTa) based on liposomes and cholera toxin combined with CpG/Alum was exploited and evaluated in mice. The results showed that humoral and cellular immune responses were induced in all the vaccination groups in two animal models. The levels of specific and neutralizing antibodies and the proliferation levels of T helper(Th) cells were significantly higher than those in the control group. The protective efficacy of the subunit vaccines evaluated in the pseudovirus in vivo infection mouse model strongly suggested that this vaccine could provide protective immunity against NiV. The neoadjuvant group showed a more protective efficacy than the CpG/Alum group. The aforementioned results indicated that the subunit vaccine could be used as a promising candidate vaccine for preventing Nipah virus infection.